2015
DOI: 10.1007/s11095-015-1697-z
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Peptide and Preservatives: Effects on Peptide Self-Interactions and Antimicrobial Efficiency In Aqueous Multi-Dose Formulations

Abstract: Peptide-preservative interactions not only affect peptide self-interactions, but also antimicrobial efficiency of the preservatives and are thus of significant relevance. Adsorption of preservatives on oligomeric states of peptides is proposed as a mechanism to explain this reduced antimicrobial efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 28 publications
(38 reference statements)
1
30
0
Order By: Relevance
“…These data support the hypothesis that hydrophobic interactions, partially associated with lipid sidechains, are driving the association in the presence of phenol and meta-cresol, but also indicates that other intermolecular interactions from the peptide backbone are playing a role in intermolecular and antimicrobial preservative-induced interactions, such as hydrophobic, pi-and hydrogen bonding. 34 To rule out the effects of bulk solution properties on the observed changes in turbidity and fluorescence blue shift, solutions of free Trp in 50 mM His buffer were characterized in the presence of the three antimicrobial preservatives. Turbidity measurement confirms no measurable change in the Trp solutions and that solubility limitations of the antimicrobial preservatives do not contribute to changes in the turbidity of the peptide solutions (Fig.…”
Section: Self-assembly Behavior Of Peptides Influenced By Preservativesmentioning
confidence: 99%
See 1 more Smart Citation
“…These data support the hypothesis that hydrophobic interactions, partially associated with lipid sidechains, are driving the association in the presence of phenol and meta-cresol, but also indicates that other intermolecular interactions from the peptide backbone are playing a role in intermolecular and antimicrobial preservative-induced interactions, such as hydrophobic, pi-and hydrogen bonding. 34 To rule out the effects of bulk solution properties on the observed changes in turbidity and fluorescence blue shift, solutions of free Trp in 50 mM His buffer were characterized in the presence of the three antimicrobial preservatives. Turbidity measurement confirms no measurable change in the Trp solutions and that solubility limitations of the antimicrobial preservatives do not contribute to changes in the turbidity of the peptide solutions (Fig.…”
Section: Self-assembly Behavior Of Peptides Influenced By Preservativesmentioning
confidence: 99%
“…31e33 Phenol and benzyl alcohol were shown to have little to no impact on the oligomer size of a linear, 40 amino acid peptide with a conjugated palmitoyl group (C 16 ) at the C-terminus, while meta-cresol was found to significantly increase oligomer size, correlated with increased attraction between oligomers in solution. 34 Awareness of these challenges have led to additional screening during the discovery and design of novel peptide therapeutics, where molecular design features incorporated by Evers et al improved polarity and conformational stability for a 39 amino acid GLP-1/glucagon coagonist peptide conjugated to a C 16 fatty acid chain, ensuring that >10 mg/mL solubility was achieved across a broad pH range in the presence of 0.5% phenol. 13 In addition to increasing solubility, the introduction of four point mutations to the 39 amino acid peptide resolved a peptide fibrillation liability that was only detected in the presence of metacresol.…”
Section: Introductionmentioning
confidence: 99%
“…The aggregation event may be induced by weak binding of the preservative to the peptide and favor an increase in the level of partially unfolded, aggregation-competent species . Furthermore, addition of preservatives can increase the attractive forces between peptide oligomers, leading to aggregate formation . Thus, a strategy for optimizing preservative-induced aggregation of a peptide might be (1) stabilization of the native conformation at potential preservative binding sites or (2) introduction of modifications that reduce the binding tendency for preservatives.…”
Section: Resultsmentioning
confidence: 99%
“…Such drug–device combinations require a low-viscosity solution, long-term chemical and physical stability, and the compatibility of the peptide with aromatic preservatives, such as phenol, m -cresol, or benzyl alcohol to inhibit the growth of microorganisms that may be introduced from repeatedly withdrawing individual use doses . Indeed, aggregation or solubility issues have been reported under certain conditions for several peptides with agonistic activity at the GLP-1, glucagon, or glucose-dependent insulinotropic peptide (GIP) receptor. Consequently, in order to maximize the probability of success during drug development, it is increasingly recognized that physical stability should be assessed as early as possible in a discovery program, to provide robust development candidates with respect to the final drug product and to physical stress conditions that will be encountered in the downstream processes. …”
Section: Introductionmentioning
confidence: 99%
“…44 Similarly, the effects of m-cresol, phenol, and benzyl alcohol on conformational stability and aggregation propensity of human growth hormone (hGH) showed m-cresol was the most destabilizing, followed by phenol, and benzyl alcohol. 9 Using a model peptide with various preservatives, Heljo et al 45 reported that m-cresol caused the most peptide destabilization, followed by phenol and benzyl alcohol. The opposite stability trend observed in this work (increasing stability of AH-adsorbed P [4] with increasing preservative hydrophobicity) may be attributed to the inherent properties of P [4] protein antigen (vs. mAbs, hGH or a peptide) as well as possible differences in solution conditions.…”
Section: Stability Profile Of Ah-adsorbed P[4] Protein Antigen In Presence Of Various Preservativesmentioning
confidence: 99%